2021
DOI: 10.3390/cancers13092242
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Risk Factors and Patterns for Early Recurrence of Pancreatic Neuroendocrine Tumors: A Multi-Institutional Study

Abstract: Background: Identifying patients at risk for early recurrence (ER) following resection for pancreatic neuroendocrine tumors (pNETs) might help to tailor adjuvant therapies and surveillance intensity in the post-operative setting. Methods: Patients undergoing surgical resection for pNETs between 1998–2018 were identified using a multi-institutional database. Using a minimum p-value approach, optimal cut-off value of recurrence-free survival (RFS) was determined based on the difference in post-recurrence surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Table 4 highlights differences in characteristics and outcomes of resected PNETs in this cohort compared to two large, independent trials conducted in USA and Europe. 6,9 Overall, the Australian cohort had lower grades and recurrences but higher operative complications.…”
Section: Comparison To Global Datamentioning
confidence: 97%
See 2 more Smart Citations
“…Table 4 highlights differences in characteristics and outcomes of resected PNETs in this cohort compared to two large, independent trials conducted in USA and Europe. 6,9 Overall, the Australian cohort had lower grades and recurrences but higher operative complications.…”
Section: Comparison To Global Datamentioning
confidence: 97%
“…The median length of hospital stay was 10 days. Forty-four patients required ICU admission post-operatively with a median length of stay of 2 days (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19).…”
Section: Perioperative Morbiditymentioning
confidence: 99%
See 1 more Smart Citation
“…pNET with highrisk factors can experience recurrence or metastasis within 16 to 18 months after surgery. [72][73][74][75][76] Therefore, some studies suggested shortening the follow-up interval or providing adjuvant therapy for pNET patients with high-risk factors. However, Barret et al [77] found that neither SSA nor cytotoxic adjuvant chemotherapy provided benefits to patients with gastrointestinal pancreatic NETs after radical resection.…”
Section: Postoperative Adjuvant Therapy For G3 Pnetmentioning
confidence: 99%
“…Nonfunctioning PNETs (NF‑PNETs) are much more common than functioning PNETs, account for approximately 70–90% of all PNETs [ 5 ]. NF‑PNETs are associated with heterogeneous biological behaviors ranging from indolent to highly aggressive [ 6 ]. The clinical outcomes are variable with the 5-year survival rates ranging from 30 to 66% [ 7 ].…”
Section: Introductionmentioning
confidence: 99%